Rah Utami Nugrahani STRATEGI PENGGUNAAN MEDIA SOSIAL SAUNG ANGKLUNG UDJO DALAM MENGKOMUNIKASIKAN ESTETIKA BAMBU - Rah Utami Nugrahani; Sylvie Nurfebiaraning (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Saung Angklung Udjo (SAU) is a performance venue that was founded in 1966 by UdjoNgalagena and hasstood until now for one of them aimed at communicating bamboo music, in this case focusing a lot onangklung, as Indonesia’s cultural wealth, especially West Java. To further develop themselves, SAU alsobegan to move in the online field, which in this case was specifically done through social media, especiallyYoutube and Instagram. To find out more about SAU’s social media strategy in communicating SAU’s aesthetics,observations, interviews and literature studies were conducted. After taking the data which is then processedby qualitative methods, the following results and discussion are obtained: SAU conducts all publicationsand documentation related to on-site performances to be uploaded via Instagram and Youtube, SAUcollaborates to increase the popularity of bamboo music, with one of them picking up composer Eka Gustiwanais able to produce fresh works that are accessible to the public, SAU re-arranged to make bamboo musicfamiliar, especially among Western music listeners, and this strategy is also generally a form of angklungpreservation in its position as Intangible Cultural Heritage of Humanity by UNESCO version which was passedin 2010.